Current studies in local-culture based ELT materials development evaluation instruments: Systematic review - ikhsanudin, ikhsanudin; Ikramunnisa, Erica; Paramita, Ratri (Politeknik Negeri Bali, 2023)
This systematic literature review was completed to investigate the status quo of evaluation instruments utilized in the development of local-culture based ELT materials in Indonesia. The main concern in this review is the validity of the evaluation instrument. This research used the PRISMA 2020 model to review the existing studies in the intended area. The data were collected from the Garuda database an official database to index articles published in Indonesia. There are 2.394 studies obtained and only 76 of them fulfil all criteria for analysis. Out of 76 studies reviewed, the results show that there are no studies that have validated their evaluation instruments. In addition, 56 studies prefer to use self-made evaluation instruments in the materials development process. Only 10 studies chose to adapt the available evaluation instrument from other sources in their development process. This review found that there is a gap that lies between the available local culture-based ELT materials evaluation instruments and the need of validity to be applied to materials development. It suggested the need of more studies in instrument development and validation to support Indonesian local-culture based ELT materials development. In the long run, the local culture will be globally well-known and accepted if the materials are available and accessible world-wide.